Prokrastinasi Akademik Mahasiswa Tingkat Akhir pada Masa Pandemi COVID-19 - Khoirunnisa, Riza Noviana; Jannah, Miftakhul; Dewi, Damajanti Kusuma; Satiningsih, Satiningsih (Universitas Negeri Surabaya, 2021)
The COVID-19 pandemic is currently affecting education bodies including universities. The negative impacts of pandemic on students’ academic lives cannot be underestimated primarily on the final-year undergraduate students who are working on their thesis. Various obstacles encountered by the students due to the distance learning applied by universities in responding to the pandemic can cause academic problems including procrastination. The main impact of academic procrastination on students is the delay in graduation that affects both the students’ future careers and the image of the university. The study aims to describe the academic procrastination of the final-year students during the COVID-19 pandemic. This was a survey research that applied saturated samples for recruiting subjects. A number of 224 final-year students were involved. Data was collected using an academic procrastination questionnaire and was analysed descriptively using a statistic program. The results showed that the academic procrastination among the participants was in the moderate category. The residence of the participants who are working on their thesis from homes indicate the connection with academic procrastination. In contrast, gender and the entry year are not proved as the factors that affect the students’ academic procrastination. Keywords: Academic procrastination, COVID-19 pandemic, students Abstrak: Pandemi COVID-19 telah berdampak pada pendidikan tinggi. Dampak negatif tidak dapat diabaikan dalam kegiatan pembelajaran terlebih pada mashasiswa semester akhir yang sedang mengerjakan skripsi. Berbagai kendala yang ditemui mahasiswa menimbulkan prokrastinasi akademik. Dampak dari prokrastinasi akade-mik adalah tertundanya kelulusan yang mempengaruhi baik masa depan mahasiswa maupun citra perguruan tinggi. Penelitian ini bertujuan untuk mengetahui gambaran prokrastinasi akademik mahasiswa tingkat akhir dalam masa pandemi COVID-19. Penelitian ini menggunakan metode survei yang merekrut subjek menggunakan teknik sampling jenuh dengan jumlah subjek penelitian sebesar 224 orang. Data dikumpulkan menggunakan skala prokrastinasi akademik dan dianalisis secara deskriptif dengan bantuan program statistik. Hasil penelitian menunjukkan prokrastinasi akademik pada subjek berada pada kategori sedang. Tempat tinggal ditemukan menjadi faktor yang berkaitan dengan prokrastinasi akademik selama mengerjakan skripsi dari rumah. Namun, jenis kelamin dan tahun masuk universitas tidak terbukti sebagai faktor yang mempengaruhi prokrastinasi akademik mahasiswa.